We Need the Largest Experiments on Earth to Achieve Our Climate Targets - Bronson W. Griscom; Susan C. Cook‐Patton; Erin Sills; Kelsey Jack; Thomas W. Crowther; Sebastien Costedoat; Christopher Field; David Hole; Lisa M. McCullough; Subhrendu K. Pattanayak; Sassan Saatchi; Will R. Turner (Global Change Biology, 2025)

Taphonomic damage obfuscates interpretation of the retroarticular region of the Asteriornis mandible - Abi Crane; Juan Benito; Albert Chen; Grace Musser; Christopher R. Torres; Julia A. Clarke; Stephan Lautenschlager; Daniel T. Ksepka; Daniel J. Field (Geobios, 2025)

Assessment of genomic diversity within and between two cryptic shiners, the West Texas shiner ( Notropis megalops ) and the Texas shiner ( Notropis amabilis ) - Kayla R. Dye; Andrew T. Fields; Megan G. Bean; Sarah M. Robertson; Christopher M. Hollenbeck; Kevin W. Conway; David S. Portnoy (Journal of Fish Biology, 2025)
The presence of cryptic species can hinder effective conservation planning and implementation, as has been the case for speciose groups of freshwater fishes that are difficult to differentiate due to conserved morphologies. The West Texas shiner Notropis megalops and the Texas shiner Notropis amabilis are a cryptic pair of leuciscids (minnows) that co‐occur in spring‐fed tributaries of the Rio Grande in Texas and Mexico. Both N. megalops and N. amabilis are listed as Species of Greatest Conservation Need by the Texas Parks and Wildlife Department. Notropis amabilis is widespread and listed as apparently secure by Texas Parks and Wildlife Department whereas N. megalops has a very limited distribution and has not been ranked by Texas Parks and Wildlife Department because of data deficiency. Morphological differences between these species have been described; however, proper identification in situ remains problematic. Furthermore, given their range of overlap there is potential for hybridization, and limited genetic data have been collected comparing the species. Therefore, reduced representation genomic and mitochondrial sequencing data were used to reassess the distinctness of the species, screen for hybridization, and characterize their relative frequencies throughout their range of overlap. Genomic analyses recovered two distinct genetic groups corresponding to the species ( F' CT = 0.89) with no evidence of admixture or introgression. The species were found to co‐occur at three sampling locations, two in the Devils River and one in the Pecos, but not in equal frequencies. Overall, these results provide data and tools for further research on N. megalops needed for accurate conservation policies and management practices.

Long‐term elevated precipitation induces grassland soil carbon loss via microbe‐plant–soil interplay - Mengmeng Wang; Xin Sun; Baichuan Cao; Nona R. Chiariello; Kathryn M. Docherty; Christopher B. Field; Qun Gao; Jessica L. M. Gutknecht; Xue Guo; Genhe He; Bruce A. Hungate; Jiesi Lei; et al. (Global Change Biology, 2023)
Global climate models predict that the frequency and intensity of precipitation events will increase in many regions across the world. However, the biosphere‐climate feedback to elevated precipitation (eP) remains elusive. Here, we report a study on one of the longest field experiments assessing the effects of eP, alone or in combination with other climate change drivers such as elevated CO 2 (eCO 2 ), warming and nitrogen deposition. Soil total carbon (C) decreased after a decade of eP treatment, while plant root production decreased after 2 years. To explain this asynchrony, we found that the relative abundances of fungal genes associated with chitin and protein degradation increased and were positively correlated with bacteriophage genes, suggesting a potential viral shunt in C degradation. In addition, eP increased the relative abundances of microbial stress tolerance genes, which are essential for coping with environmental stressors. Microbial responses to eP were phylogenetically conserved. The effects of eP on soil total C, root production, and microbes were interactively affected by eCO 2 . Collectively, we demonstrate that long‐term eP induces soil C loss, owing to changes in microbial community composition, functional traits, root production, and soil moisture. Our study unveils an important, previously unknown biosphere‐climate feedback in Mediterranean‐type water‐limited ecosystems, namely how eP induces soil C loss via microbe‐plant–soil interplay.

Spatial and temporal variability of per- and polyfluoroalkyl substances (PFAS) in environmental media of a small pond: Toward an improved understanding of PFAS bioaccumulation in fish - Abbi S. Brown; Xiaoyan Yun; Erica R. McKenzie; Christopher G. Heron; Jennifer A. Field; Christopher J. Salice (Science of The Total Environment, 2023)

Radiation Oncology Virtual Education Rotation (ROVER) 2.0 for Residents: Implementation and Outcomes - Navjot K. Sandhu; Elham Rahimy; Ryan Hutten; Utkarsh Shukla; Anne Rajkumar-Calkins; Jacob A. Miller; Rie Von Eyben; Christopher R. Deig; Jean-Pierre Obeid; Rachel B. Jimenez; Emma C. Fields; Erqi L. Pollom; et al. (Journal of Cancer Education, 2023)

Enhancing the review process in global environmental assessments: The case of the IPCC - Jean P. Palutikof; Sarah L. Boulter; Christopher B. Field; Katharine J. Mach; Martin R. Manning; Michael D. Mastrandrea; Leo Meyer; Jan C. Minx; Joy J. Pereira; Gian-Kasper Plattner; Suzana Kahn Ribeiro; Youba Sokona; et al. (Environmental Science & Policy, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

Mercury exposure of tidal marsh songbirds in the northeastern United States and its association with nest survival - Katharine J. Ruskin; Garth Herring; Collin A. Eagles-Smith; Alyssa B. Eiklor; Chris S. Elphick; Matthew A. Etterson; Christopher R. Field; Rebecca A. Longenecker; Adrienne I. Kovach; W. Gregory Shriver; Jennifer Walsh; Brian J. Olsen (Ecotoxicology, 2022)

High uncertainty over the future of tidal marsh birds under current sea-level rise projections - Brian T. Klingbeil; Jonathan B. Cohen; Maureen D. Correll; Christopher R. Field; Thomas P. Hodgman; Adrienne I. Kovach; Erika E. Lentz; Brian J. Olsen; W. Gregory Shriver; Whitney A. Wiest; Chris S. Elphick (Biodiversity and Conservation, 2021)

Fire affects the taxonomic and functional composition of soil microbial communities, with cascading effects on grassland ecosystem functioning - Sihang Yang; Qiaoshu Zheng; Yunfeng Yang; Mengting Yuan; Xingyu Ma; Nona R. Chiariello; Kathryn M. Docherty; Christopher B. Field; Jessica L. M. Gutknecht; Bruce A. Hungate; Audrey Niboyet; Xavier Le Roux; et al. (Global Change Biology, 2020)
Fire is a crucial event regulating the structure and functioning of many ecosystems. Yet few studies have focused on how fire affects taxonomic and functional diversities of soil microbial communities, along with changes in plant communities and soil carbon (C) and nitrogen (N) dynamics. Here, we analyze these effects in a grassland ecosystem 9 months after an experimental fire at the Jasper Ridge Global Change Experiment site in California, USA. Fire altered soil microbial communities considerably, with community assembly process analysis showing that environmental selection pressure was higher in burned sites. However, a small subset of highly connected taxa was able to withstand the disturbance. In addition, fire decreased the relative abundances of most functional genes associated with C degradation and N cycling, implicating a slowdown of microbial processes linked to soil C and N dynamics. In contrast, fire stimulated above‐ and belowground plant growth, likely enhancing plant–microbe competition for soil inorganic N, which was reduced by a factor of about 2. To synthesize those findings, we performed structural equation modeling, which showed that plants but not microbial communities were responsible for significantly higher soil respiration rates in burned sites. Together, our results demonstrate that fire ‘reboots’ the grassland ecosystem by differentially regulating plant and soil microbial communities, leading to significant changes in soil C and N dynamics.

Framework for quantifying population responses to disturbance reveals that coastal birds are highly resilient to hurricanes - Christopher R. Field; Katharine J. Ruskin; Jonathan B. Cohen; Thomas P. Hodgman; Adrienne I. Kovach; Brian J. Olsen; W. Gregory Shriver; Chris S. Elphick (Ecology Letters, 2019)
Changes in the frequency and severity of extreme weather may introduce new threats to species that are already under stress from gradual habitat loss and climate change. We provide a probabilistic framework that quantifies potential threats by applying concepts from ecological resilience to single populations. Our approach uses computation to compare disturbance–impacted projections to a population's normal range of variation, quantifying the full range of potential impacts. We illustrate this framework with projection models for coastal birds, which are commonly depicted as vulnerable to disturbances, especially hurricanes and oil spills. We found that populations of coastal specialists are resilient to extreme disturbances, with high resistance to the effects of short‐term reductions in vital rates and recovery within 20 years. Applying the general framework presented here across disturbance‐prone species and ecosystems would improve understanding of population resilience and generate specific projections of resilience that are needed for effective conservation planning.

Genetic modifiers of radon-induced lung cancer risk: a genome-wide interaction study in former uranium miners - Albert Rosenberger; Rayjean J. Hung; David C. Christiani; Neil E. Caporaso; Geoffrey Liu; Stig E. Bojesen; Loic Le Marchand; Ch. A. Haiman; Demetrios Albanes; Melinda C. Aldrich; Adonina Tardon; G. Fernández-Tardón; et al. (International Archives of Occupational and Environmental Health, 2018)

Experimental fire increases soil carbon dioxide efflux in a grassland long‐term multifactor global change experiment - Aaron L. Strong; Tera P. Johnson; Nona R. Chiariello; Christopher B. Field (Global Change Biology, 2017)
Numerous studies have demonstrated that soil respiration rates increase under experimental warming, although the long‐term, multiyear dynamics of this feedback are not well constrained. Less is known about the effects of single, punctuated events in combination with other longer‐duration anthropogenic influences on the dynamics of soil carbon (C) loss. In 2012 and 2013, we assessed the effects of decadal‐scale anthropogenic global change – warming, increased nitrogen (N) deposition, elevated carbon dioxide ( CO 2 ), and increased precipitation – on soil respiration rates in an annual‐dominated Mediterranean grassland. We also investigated how controlled fire and an artificial wet‐up event, in combination with exposure to the longer‐duration anthropogenic global change factors, influenced the dynamics of C cycling in this system. Decade‐duration surface soil warming (1–2 °C) had no effect on soil respiration rates, while +N addition and elevated CO 2 concentrations increased growing‐season soil CO 2 efflux rates by increasing annual aboveground net primary production ( NPP ) and belowground fine root production, respectively. Low‐intensity experimental fire significantly elevated soil CO 2 efflux rates in the next growing season. Based on mixed‐effects modeling and structural equation modeling, low‐intensity fire increased growing‐season soil respiration rates through a combination of three mechanisms: large increases in soil temperature (3–5 °C), significant increases in fine root production, and elevated aboveground NPP . Our study shows that in ecosystems where soil respiration has acclimated to moderate warming, further increases in soil temperature can stimulate greater soil CO 2 efflux. We also demonstrate that punctuated short‐duration events such as fire can influence soil C dynamics with implications for both the parameterization of earth system models ( ESM s) and the implementation of climate change mitigation policies that involve land‐sector C accounting.

High‐resolution tide projections reveal extinction threshold in response to sea‐level rise - Christopher R. Field; Trina S. Bayard; Carina Gjerdrum; Jason M. Hill; Susan Meiman; Chris S. Elphick (Global Change Biology, 2017)
Sea‐level rise will affect coastal species worldwide, but models that aim to predict these effects are typically based on simple measures of sea level that do not capture its inherent complexity, especially variation over timescales shorter than 1 year. Coastal species might be most affected, however, by floods that exceed a critical threshold. The frequency and duration of such floods may be more important to population dynamics than mean measures of sea level. In particular, the potential for changes in the frequency and duration of flooding events to result in nonlinear population responses or biological thresholds merits further research, but may require that models incorporate greater resolution in sea level than is typically used. We created population simulations for a threatened songbird, the saltmarsh sparrow ( Ammodramus caudacutus ), in a region where sea level is predictable with high accuracy and precision. We show that incorporating the timing of semidiurnal high tide events throughout the breeding season, including how this timing is affected by mean sea‐level rise, predicts a reproductive threshold that is likely to cause a rapid demographic shift. This shift is likely to threaten the persistence of saltmarsh sparrows beyond 2060 and could cause extinction as soon as 2035. Neither extinction date nor the population trajectory was sensitive to the emissions scenarios underlying sea‐level projections, as most of the population decline occurred before scenarios diverge. Our results suggest that the variation and complexity of climate‐driven variables could be important for understanding the potential responses of coastal species to sea‐level rise, especially for species that rely on coastal areas for reproduction.

Seasonal fecundity is not related to geographic position across a species’ global range despite a central peak in abundance - Katharine J. Ruskin; Matthew A. Etterson; Thomas P. Hodgman; Alyssa C. Borowske; Jonathan B. Cohen; Chris S. Elphick; Christopher R. Field; Rebecca A. Kern; Erin King; Alison R. Kocek; Adrienne I. Kovach; Kathleen M. O’Brien; et al. (Oecologia, 2017)

Loss of whole-tree hydraulic conductance during severe drought and multi-year forest die-off - William R. L. Anderegg; Leander D. L. Anderegg; Joseph A. Berry; Christopher B. Field (Oecologia, 2014)

Drought's legacy: multiyear hydraulic deterioration underlies widespread aspen forest die‐off and portends increased future risk - William R. L. Anderegg; Lenka Plavcová; Leander D. L. Anderegg; Uwe G. Hacke; Joseph A. Berry; Christopher B. Field (Global Change Biology, 2013)
Forest mortality constitutes a major uncertainty in projections of climate impacts on terrestrial ecosystems and carbon‐cycle feedbacks. Recent drought‐induced, widespread forest die‐offs highlight that climate change could accelerate forest mortality with its diverse and potentially severe consequences for the global carbon cycle, ecosystem services, and biodiversity. How trees die during drought over multiple years remains largely unknown and precludes mechanistic modeling and prediction of forest die‐off with climate change. Here, we examine the physiological basis of a recent multiyear widespread die‐off of trembling aspen ( P opulus tremuloides ) across much of western N orth A merica. Using observations from both native trees while they are dying and a rainfall exclusion experiment on mature trees, we measure hydraulic performance over multiple seasons and years and assess pathways of accumulated hydraulic damage. We test whether accumulated hydraulic damage can predict the probability of tree survival over 2 years. We find that hydraulic damage persisted and increased in dying trees over multiple years and exhibited few signs of repair. This accumulated hydraulic deterioration is largely mediated by increased vulnerability to cavitation, a process known as cavitation fatigue. Furthermore, this hydraulic damage predicts the probability of interyear stem mortality. Contrary to the expectation that surviving trees have weathered severe drought, the hydraulic deterioration demonstrated here reveals that surviving regions of these forests are actually more vulnerable to future droughts due to accumulated xylem damage. As the most widespread tree species in N orth A merica, increasing vulnerability to drought in these forests has important ramifications for ecosystem stability, biodiversity, and ecosystem carbon balance. Our results provide a foundation for incorporating accumulated drought impacts into climate–vegetation models. Finally, our findings highlight the critical role of drought stress accumulation and repair of stress‐induced damage for avoiding plant mortality, presenting a dynamic and contingent framework for drought impacts on forest ecosystems.

The IPCC AR5 guidance note on consistent treatment of uncertainties: a common approach across the working groups - Michael D. Mastrandrea; Katharine J. Mach; Gian-Kasper Plattner; Ottmar Edenhofer; Thomas F. Stocker; Christopher B. Field; Kristie L. Ebi; Patrick R. Matschoss (Climatic Change, 2011)

Baseline Ecological Risk Assessment of the Calcasieu Estuary, Louisiana: Part 3. An Evaluation of the Risks to Benthic Invertebrates Associated With Exposure to Contaminated Sediments - Donald D. MacDonald; Christopher G. Ingersoll; Nile E. Kemble; Dawn E. Smorong; Jesse A. Sinclair; Rebekka Lindskoog; Gary Gaston; Denise Sanger; R. Scott Carr; James Biedenbach; Ron Gouguet; John Kern; et al. (Archives of Environmental Contamination and Toxicology, 2011)

Coordinated approaches to quantify long‐term ecosystem dynamics in response to global change - YIQI LUO; JERRY MELILLO; SHULI NIU; CLAUS BEIER; JAMES S. CLARK; AIMÉE T. CLASSEN; ERIC DAVIDSON; JEFFREY S. DUKES; R. DAVE EVANS; CHRISTOPHER B. FIELD; CLAUDIA I. CZIMCZIK; MICHAEL KELLER; et al. (Global Change Biology, 2011)
Many serious ecosystem consequences of climate change will take decades or even centuries to emerge. Long‐term ecological responses to global change are strongly regulated by slow processes, such as changes in species composition, carbon dynamics in soil and by long‐lived plants, and accumulation of nutrient capitals. Understanding and predicting these processes require experiments on decadal time scales. But decadal experiments by themselves may not be adequate because many of the slow processes have characteristic time scales much longer than experiments can be maintained. This article promotes a coordinated approach that combines long‐term, large‐scale global change experiments with process studies and modeling. Long‐term global change manipulative experiments, especially in high‐priority ecosystems such as tropical forests and high‐latitude regions, are essential to maximize information gain concerning future states of the earth system. The long‐term experiments should be conducted in tandem with complementary process studies, such as those using model ecosystems, species replacements, laboratory incubations, isotope tracers, and greenhouse facilities. Models are essential to assimilate data from long‐term experiments and process studies together with information from long‐term observations, surveys, and space‐for‐time studies along environmental and biological gradients. Future research programs with coordinated long‐term experiments, process studies, and modeling have the potential to be the most effective strategy to gain the best information on long‐term ecosystem dynamics in response to global change.

Interactive Effects of Fire, Elevated Carbon Dioxide, Nitrogen Deposition, and precipitation on a California Annual Grassland - Hugh A. L. Henry; Nona R. Chiariello; Peter M. Vitousek; Harold A. Mooney; Christopher B. Field (Ecosystems, 2006)

Species‐specific responses of plant communities to altered carbon and nutrient availability - Geeske Joel; F. Stuart Chapin; Nona R. Chiariello; Susan S. Thayer; Christopher B. Field (Global Change Biology, 2001)
Summary In a field microcosm experiment, species‐specific responses of aboveground biomass of two California annual grassland communities to elevated CO 2 and nutrient availability were investigated. One community grows on shallow, nutrient‐poor serpentine‐derived soil whereas the other occurs on deeper, modestly fertile sandstone/greenstone‐derived substrate. In most species, CO 2 effects did not appear until late in the growing season, probably because the elevated CO 2 increased water‐use‐efficiency easing, the onset of the summer drought. Responses of aboveground biomass to elevated CO 2 differed depending on nutrient availability. Similarly, biomass responses to nutrient treatments differed depending on the CO 2 status. For the majority of the species, production increased most under elevated CO 2 with added nutrients (N,P,K, and micro nutrients). Some species were losers under conditions that increased overall community production, including Bromus hordeaceus in the serpentine community (negative biomass response under elevated CO 2 ) and Lotus wrangelianus in both communities (negative biomass response with added nitrogen). Treatment and competitive effects on species‐specific biomass varied in both magnitude and direction, especially in the serpentine community, significantly affecting community structure. Individual resource environments are likely to be affected by neighbouring plants, and these competitive interactions complicate predictions of species' responses to elevated CO 2 .

Introduction - Joseph A. Berry; Christopher B. Field; Arthur R. Grossman (Photosynthesis Research, 2001)

Plant species-specific changes in root-inhabiting fungi in a California annual grassland: responses to elevated CO 2 and nutrients - Matthias C. Rillig; Michael F. Allen; John N. Klironomos; Nona R. Chiariello; Christopher B. Field (Oecologia, 1998)